The Effect Of Education And Training (Diklat) On The Performance Of State Civil Servants (ASN) In Indonesia: A Comparative Review Based On Empirical Studies - Anna Qomariyah; Nur Wening (Jurnal Ekuisci, 2025)
Background. The effectiveness of bureaucracy and public services depends on improving the performance of the State Civil Apparatus (ASN). Aims. Education and training are considered strategic tools to achieve these goals. However, empirical research has found various findings regarding the direct influence of training on performance. Methods. In an effort to study the relationship between training and ASN performance, a comparative review of a number of quantitative and qualitative studies was conducted from 2020 to 2025. Result. The analysis reveals that, although many studies demonstrate a positive and significant influence of training, other studies have found that this influence is only partial. Additional variables, such as work discipline, competence, work environment, and leadership, are identified in this analysis as factors that moderate and mediate the relationship. Conclusion. In summary, the success of training depends on the organizational context, the design of training programs, and collaboration with other components that support performance.